Space Mission Characterization And Analysis For University Cubesat - Noor, Nursyazatul Eylia Mohd (Universiti Sains Malaysia, 2017)
For this research, the secondary mission for the MYSat-Cubesat is developed with intention to attract the targeted group to fund the mission. The development of the secondary mission for this nano satellite would benefit not only in term of funding but also gain public awareness and interest about this cubesat. The research for selecting the suitable secondary mission is done by considering the objective of the mission and the requirements. The public interest of the Malaysia toward science, technology and innovation also is taken into account to create a mission that be able to attract their interest. The development of the secondary mission is done by conducting the experiment after the suitable secondary mission has been decided. It including the component performance and reliability to carried out the secondary mission. The analysis of the result is performed afterward.